When Solidarity is Trampled by Religious Sentiment: Outlining Indonesian Muslim Solidarity toward Rohingya Refugees - Siti Aliyuna Pratisti; Taufik Hidayat; Deasy Silvya Sari (Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
The Rohingya crisis in Myanmar has drawn international attention due to gross violations of human rights, which have occurred in the conflict. This condition forces the Rohingya to flee from conflict areas in the attempt to seek protection from neighbouring countries including Indonesia. To deal with the refugees, the Indonesian government, alongside Muslim organizations, have taken immediate steps in tackling the crisis. However, behind the humanitarian solidarity lays a critical problem related to the religious sentiment toward the Buddhist community in Indonesia. The sentiment that tarnished the humanitarian principles and threatened Indonesian multiculturalism showed the versatile side of identity. To provide a better understanding of identity-based conflict, this article explored how a group’s sense of collectivity can easily turn into sentiment. By conducting multiple interviews with the representatives of Muslim Organizations and also collecting secondary data related to the Islam conservative agenda, this paper aimed to outline the paradox of Indonesian Muslim response toward the Rohingya’s refugees crisis. Using Ross’s theories of identity conflict and using Galtung conception of social conflict, the findings concluded that religious sentiment in Indonesia during the Rohingya’s refugee crisis are led by blind fanaticism toward certain religious beliefs that bitterly trample the nation’s sense of solidarity.